Gestión por procesos una herramienta para incrementar la calidad académica en la carrera de ingeniería comercial de la universidad técnica de cotopaxi en el periodo 2014-2015 - Borja Ruiz, Daniel Eduardo (2015)
Management processes is a tool to increase the academic quality in the Commercial Engineering Career of the Cotopaxi Technical University, which has the general objective to develop a processes manual by using tools to gather information about executed activities in the four fundamental axes like: Teaching, Researching, Entailment, and Management, as is generally known, the inconsistencies exist in the use of resources and time in the executed processes at the career, so the main problem of the subject matter of our investigation. Every fundamental axe has its respective value strings which demonstrate the complexity of its structure, showing macro-processes, processes, threads and activities….